Not quite in the public interest: Bennett, P & Murphy, S (1997) Psychology and Health Promotion. Buckingham: Open University Press. ISBN. 0-335-19765-5 pbk. 184 pages. - Bhagwanjee, Anil (PINS-Psychology in Society, 2026)
While health promotion draws on a broad range of disciplines and perspectives, psychological theory has undoubtedly informed much of the science and practice of health promotion. Notwithstanding this, texts that demonstrate and advance the application of psychological theory to health promotion practice are relatively scarce. This is Bennett and Murphy's central goal, and as such this text represents a welcome contribution to the field.